Association of polymorphisms of genes SLC30A8 and MC4R with the prognosis of the development of type 2 diabetes mellitus - E. S. Mel’nikova; S. V. Mustafina; O. D. Rymar; A. A. Ivanova; L. V. Shcherbakova; M. Bobak; S. K. Maljutina; M. I. Voevoda; V. N. Maksimov (Сахарный диабет)
BACKGROUND: The prevalence of Type 2 diabetes mellitus (T2DM) has reached epidemic proportions and it is estimated to affect over 400 million people worldwide. Moreover, the incidence of diabetes is expected to continue to rise and it is projected to affect nearly one of the three individuals by the year 2050. These alarming projections suggest that there is an urgent need for the development and implementation of novel prevention and treatment strategies to combat the rise in T2DM.AIM: To study the possibility of using polymorphisms of genes SLC30A8 and MC4R as markers for predicting the development of T2D in the population of Novosibirsk.MATERIALS AND METHODS: On the basis of prospective follow-up of a representative population sample of residents of Novosibirsk (The HAPIEE Project), 2 groups were formed according to the “case-control” principle (case — people who had diabetes mellitus 2 over 10 years of follow-up, and control — people who did not developed disorders of carbohydrate metabolism). T2D group (n = 443, mean age 56.2 ± 6.7 years, men — 29.6%, women — 70.4%), control group (n = 532, mean age 56.1 ± 7.1 years, men — 32.7%, women — 67.3%). DNA was isolated by phenol-chloroform extraction. Genotyping was performed by the method of polymerase chain reaction with subsequent analysis of restriction fragment length polymorphism, polymerase chain reaction in real time. Statistical processing was carried out using the SPSS 16.0 software package.RESULTS: Genotype TT rs13266634 of the SLC30A8 gene was associated with the risk of developing T2D (relative risk — RR 1.51, 95% confidence interval — CI 1.11–2.05, p =0.008). The CC genotype rs13266634 of the SLC30A8 gene was associated with a protective effect against T2D (RR 0.57, 95% CI 0.35–0.92, p=0.026). No significant effect of rs17782313 of the MC4R gene on the risk of developing T2D was found.CONCLUSION: The rs13266634 polymorphism of the SLC30A8 gene confirmed its association with the prognosis of the development of T2D, which indicates the possibility of considering it as a candidate for inclusion in a diabetes risk score. The association between polymorphisms rs17782313 of the MC4R gene and the prognosis of the development of T2D was not found.